Anti-Bullying LMS Design for a Safe Learning Environment in Higher Education - Rejekiningsih, Triana; Hidayatulloh, Muhammad Muslim (JTP - Jurnal Teknologi Pendidikan, 2025)
Bullying in higher education poses significant threats to students’ right to feel safe, disrupts psychological well-being, and undermines the achievement of Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education) and Goal 16 (Peace, Justice, and Strong Institutions). This study aims to (1) identify the prevalence and forms of bullying in higher education, and (2) design an anti-bullying education program based on a Learning Management System (LMS) to enhance campus safety and support SDGs. A descriptive qualitative case study was conducted with 15 students, 10 lecturers, and 5 educational staff. Data were collected through participant observation, in-depth interviews, and campus policy document analysis, and analyzed thematically. Findings reveal that 36.7% of students experienced verbal abuse, 20% experienced online humiliation, and 26.7% were socially excluded. Bullying manifests in physical, verbal, psychological, and cyber forms, negatively affecting mental health, well-being, and academic achievement. The proposed LMS-based anti-bullying education incorporates structured learning modules on bullying types, impacts, and prevention strategies; online training for students and educators; discussion forums; integrated case reporting mechanisms; and periodic evaluations via questionnaires and data analysis. The system enhances awareness, facilitates anonymous reporting, and fosters active participation in creating a safe campus environment. This study underscores the potential of LMS as a strategic platform for inclusive, evidence-based anti-bullying interventions, contributing to the fulfillment of students’ rights and supporting the realization of SDG targets.